The Landscape of Gene Expression and Molecular Regulation Following Spinal Cord Hemisection in Rats - Yu, Bin; Yao, Chun; Wang, Yongjun; Mao, Susu; Wang, Yaxian; Wu, Ronghua; Feng, Wei; Chen, Yanping; Yang, Jian; Xue, Chengbin; Liu, Dong; Ding, Fei; et al. (Frontiers in Molecular Neuroscience, 2019)
Spinal cord injury (SCI) is a challenging clinical problem worldwide. The cellular state and molecular expression in spinal cord tissue after injury are extremely complex and closely related to functional recovery. However, the spatial and temporal changes of gene expression and regulation in various cell types after SCI are still unclear. Here, we collected the rostral and caudal regions to the lesion at 11 time points over a period of 28 days after rat hemisection SCI. Combining whole-transcriptome sequencing and bioinformatic analysis, we identified differentially expressed genes (DEGs) between spinal cord tissue from injured and sham-operated animals. Significantly altered biological processes were enriched from DEGs in astrocytes, microglia, oligodendrocytes, immune cells, and vascular systems after SCI. We then identified dynamic trends in these processes using the average expression profiles of DEGs. Gene expression and regulatory networks for selected biological processes were also constructed to illustrate the complicate difference between rostral and caudal tissues. Finally, we validated the expressions of some key genes from these networks, including α-synuclein, heme oxygenase 1, bone morphogenetic protein 2, activating transcription factor 3, and leukemia inhibitory factor. Collectively, we provided a comprehensive network of gene expression and regulation to shed light on the molecular characteristics of critical biological processes that occur after SCI, which will broaden the understanding of SCI and facilitate clinical therapeutics for SCI.